Process for producing a component from metal - GEGNER JURGEN (2003)
A process for producing a component of metal includes a) carrying out a heat treatment to harden the component, which ends with a heating process, especially with a tempering or microstructural transformation process, at a given temperature (TE ); carrying out at least machining of the component at room temperature (TU ) in order to provide its desired geometrical shape; and c) subsequent heating of the component to a temperature (T) which is greater than room temperature (TU ).